Adherence to anti-hypertensive medication regimens among patients attending the G.P.H.A. Hospital in Takoradi - Ghana. - Jambedu, Haruna Ahmed (2011)
A Thesis submitted to the Department of Clinical and Social Pharmacy, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science.